The Effects of Auditing Standard No. 18 on Audit Fees - Caruso, James (2017)
Auditing standard no. 18 was released for all audits conducted after December 15th, 2014. This release consisted of new auditing standards and amendments regarding the overall risk assessment process conducted in an audit. Additional standards were implemented to heighten the attention and evaluation of related party transactions, significant unusual transactions and transactions between executives. The following research paper investigates the economic effects for firms operating in the U.S after the new standards were introduced. The Public Company Accounting Oversight Board expects audit fees to increase, however lack quantitative evidence to support to their predictions. The following analysis finds that there was a significant increase in audit fees for the average firm operating in the U.S after auditing standard no. 18 is implemented. Significant increases took place for firms with special and unusual transactions and firms of smaller size based on total assets. Additionally, firms of complex nature measured by foreign operations and the number of business segments show no significant increases in fees once the new standards are implemented.